Epistemologi Pendidikan Islam Berbasis Tauhid: Tantangan dan Relevansinya di Era Digital - Agi Kurniawan; Ena Sumpena; Salman Fathurohman; Ridwan Abdalloh (TA'DIB: Jurnal Pendidikan Agama Islam, 2023)
This study aims to analyze the epistemology of Islamic education based on tawhid and to examine its challenges and relevance in the digital era. The rapid development of digital technology has transformed the ways in which people acquire, manage, and disseminate knowledge, thereby creating a need to reconstruct the paradigm of Islamic education so that it remains rooted in divine values. This research employs a qualitative approach with a library research design, drawing upon various scholarly works related to Islamic epistemology, tawhid-based education, and digital transformation in education. The data were analyzed using content analysis techniques to identify the relationship between the concept of tawhid and the dynamics of contemporary learning. The findings reveal that tawhid serves as an epistemological foundation that positions revelation as the primary source of knowledge, which is then integrated with reason and empirical experience in the educational process. The main challenges in the digital era include information overload, a crisis of scholarly authority, the secularization of knowledge, and the weakening of spiritual value internalization in online learning environments. Nevertheless, the digital era also offers significant opportunities for the development of Islamic education through the utilization of technology as a medium for broader and more inclusive knowledge dissemination. This study affirms that the epistemology of Islamic education based on tawhid remains relevant as a foundation for building an integrative, critical, and value-oriented educational system aimed at forming individuals who are faithful, knowledgeable, and morally grounded amid the ongoing changes of the modern era.